Aplikasi Mobile Your Job MBTI (Myers-Briggs Indicator) Menggunakan Algoritma Fisher-Yates Shuffle - Septi Andryana; Aris Gunaryati; Bimo Salasa Putra (STMIK Budi Darma, 2021)
Work is something that everyone will do. This is because by working we will earn money that can make us able to fulfill our needs. But sometimes there are still quite a lot of people out there who don't even know what job is right for them. Therefore the author designed an application called Your Job based on Android, this application will provide suitable job recommendations based on the person's personality. In this study using the fisher-yates shuffle algorithm. Fisher-Yates shuffle algorithm can be applied to randomization of questions. The design of this application also uses the MBTI (Myers-Briggs Indicator) method to make it easier to determine a person's personality. After doing it to several people about this application. They gave a very good response, it is certain that the fisher-ystes shuffle algorithm runs well in randomizing the questions and using the MBTI method the accuracy level is almost 100% accurate.